Language barriers and their consequences in healthcare: a qualitative case study of Nepali migrants in Finland - Shrwan Kumar Khanal (BMC Health Services Research)
Abstract Background Migrants face multiple barriers in using healthcare, with language being a major obstacle. In Finland, research on minority migrant groups, such as Nepali migrants, remains limited. This study examines how language barriers, informal networks, and interpreter services affect healthcare use among the Nepali migrant community, a small but growing group in Finland. Methods This qualitative study employed semi-structured interviews with 27 working age Nepali migrants in Finland. The data was collected between February and August 2023 and was analysed thematically to identify barriers to healthcare use. Results Limited language proficiency restricted participants’ ability to navigate healthcare services, comprehend medical instructions, and communicate effectively with providers, which in some cases contributed to experiences of perceived discrimination. Consequently, many relied on informal networks, such as employers or co-ethnic communities, for healthcare information, often receiving misleading or incomplete guidance. The shortage of professional interpreters further worsened these challenges, while privacy concerns discouraged the use of community-based interpreters. Moreover, participants’ limited awareness of their healthcare rights as employees reinforced their dependence and increased their vulnerability to labour exploitation within migrant communities. Conclusions Language barriers not only affect direct communication but also contribute to systemic inequalities in healthcare access by reinforcing reliance on informal support structures. Addressing these challenges requires providing language training programs, enhancing the availability of professional interpreters, and ensuring that new migrants are informed about their healthcare entitlements through effective integration programs tailored to minority migrants.